Strong Convergence Theorems for a Finite Family of λi-Strict Pseudocontractions in 2-Uniformly Smooth Banach Spaces by Metric Projections - Xin-dong Liu; Shih-sen Chang; Xiong-rui Wang (Journal of Applied Mathematics)
A new hybrid projection algorithm is considered for a finite family of λi-strict pseudocontractions. Using the metric projection, some strong convergence theorems of common elements are obtained in a uniformly convex and 2-uniformly smooth Banach space. The results presented in this paper improve and extend the corresponding results of Matsushita and Takahshi, 2008, Kang and Wang, 2011, and many others.